Gaya Bahasa Perbandingan dalam Pepatah Petitih Pemberian Gelar Adat pada Upacara Perkawinan di Desa Danau Kecamatan Kuantan Hilir Seberang - Wibela Cahaya; Charlina Charlina; Auzar Auzar (Departement of Mathematics Education, 2023)
This research is motivated with the aim of describe the language style comparisons in the awarding of tradisional titles at the wedding ceremony in Danau Village, Kuantan Hilir Seberang District. The data collection technique out by all.com, the author of this study, was to Moleong (2007:11) states descriptive qualitative reseatch methods are data colleted in theform of words, not number. This method is in accordance with the research that the author did regarding the proverb used in giving customary titles at the marriage ceremony in Danau Village, Kuantan Hilir Seberang District. The source of the data in this research is the proverbs spoken by ninik mamak in giving the customery title at the wedding ceremony. This study found 4 comparative language styles consisting of: allegory language style, personification stle, hyperbole stle, and euphemism style.